Våtmarker för näringsretention i Lillån : var bör de ligga och vilken effekt kan vi förvänta - Pettersson, Malin (SLU/Dept. of Soil Sciences, 2006)
Construction of wetlands in the agricultural landscape may reduce nitrogen and phosphorus transfer to streams, thereby reducing the eutrophication of lakes and seas. The agriculturalstream Lillån, a tributary to stream Sagån, ends up in Lake Mälaren and is transporting large amounts of these plant nutrients. The aim of this study was to estimate how hypothetical wetlands of different size and location may reduce nitrogen and phosphorus load from stream Lillån. Estimated nutrient retention in several small wetlands was compared to retention in a single large wetland based on existing data from the agricultural stream and from a nearby smaller stream. Retention in the stream was suggested to decrease along with the nutrient concentration in the water. Total nitrogen was found to be retained more efficiently with one large wetland located far downstream in the system (13 %) compared to several small wetlands high up in the stream (8 %). Nutrient retention would be largely influenced based on the assumed effect on the quality of water leaving all the small wetlands. However, size and location turned out to be less important for phosphorus retention (40 % with one large wetland compared to 38 % with several small wetlands) based on adopted assumptions. These included that retention of phosphorus in the stream was more or less negligible compared to the retention in wetlands. Nitrogen retention was estimated to be more efficient in larger wetlands (111 kg ha-1 yr-1) compared to smaller (95 kg ha-1 yr-1), except for in the winter period December to April. In this period nitrogen retention was found to be practically the same in both large and small wetlands.